Chlorine isotope variations in the hyper-acid lake system of Poás volcano, Costa Rica - Rodríguez, Alejandro (2013)
This study provides some datasets of the most salient geochemical signatures of the acid lake and their strongly uctuating behaviour observed over the last 30 years.